Ozone exposure and blood transcriptome: A randomized, controlled, crossover trial among healthy adults. (May 2022) - Du, Xihao; Niu, Yue; Wang, Cuiping; Wang, Weidong; Liu, Cong; Meng, Xia; Chu, Chen; Chen, Renjie; Kan, Haidong
Graphical abstract: Highlights: The randomized, crossover trial design has advantage of strong causal inference. First study evaluated genome-wide mRNA following ozone exposure using RNA-seq. Ozone exposure led to significant dysregulation of circulating transcriptome. Affected mRNA plays important roles in various cardiopulmonary diseases. Abstract: Rationale: Transcriptome-wide analysis is powerful in studying systemic RNA changes following environmental exposures. However, impacts of ozone inhalation on circulating transcriptome have not yet been examined. Objectives: To explore the impact of acute ozone exposure on circulating transcriptome using RNA sequencing (RNA-seq). Methods: We recruited 32 healthy young adults in a randomized, crossover, controlled exposure trial. Each participant completed two 2-h exposure sessions of ozone (200 ppb) and clean air, respectively. Blood samples were collected at the end of each session and were used for RNA-seq. The differentially expressed genes associated with ozone exposure were assessed using Bayesian adjusted statistics from linear models in the limma R package. Results: A total of 29 participants finished this trial and donated their blood samples for transcriptome analysis. The average concentration of ozone was 7.8 ± 2.6 ppb under clean air and 201.1 ± 1.7 ppb under ozone exposure session. A total of 1899 genes were significantly changed (1067 up-regulated and 832 down-regulated) by ozone exposure at a false discovery rate < 0.05, in which 403 genes had a fold change of > 1.2 or < 0.8. The top 10 terms of biological processes showed that most of the differentially expressed genes were related to various functions, such as neutrophil degranulation, immune response, and neutrophil activation. Pathway enrichment analysis showed dozens of pathways were dysregulated after ozone exposure, including mitochondrial dysfunction, and glucocorticoid receptor signaling. Conclusion: For the first time this trial characterized the genome-wide changes of mRNA in response to ozone exposure. We identified a range of differentially expressed genes that were involved in dozens of biological processes and pathways, providing novel biological insights into the systemic health effects of ozone.